Altered Regional Homogeneity in Patients With Corneal Ulcer: A Resting-State Functional MRI Study - Xu, Man-Wei; Liu, Hui-Min; Tan, Gang; Su, Ting; Xiang, Chu-Qi; Wu, Wei; Li, Biao; Lin, Qi; Xu, Xiao-Wei; Min, You-Lan; Liu, Wen-feng; Gao, Gui-Ping; et al. (Frontiers in Neuroscience, 2019)
Objective: To investigate the potential regional homogeneity (ReHo) brain activity changes in patients with corneal ulcer (CU) and their possible relationship with clinical symptoms. Materials and methods: 40 patients with CU (26 men and 14 women), and 40 healthy controls (HCs) (26 men and 14 women) closely matched in age, sex and weight underwent resting-state functional MRI scans respectively. The ReHo method was applied to evaluate synchronous neural activity changes. Receiver operating characteristic curve (ROC curve) was used to show high test-retest stability and high degree of sensitivity and specificity.. We utilized the correlation analysis to calculate the relationship between the average ReHo signal values in different brain areas and the clinical symptoms in CU patients. Results: Compared with the HCs, CU patients had significantly increased ReHo values in right cerebellum posterior lobe, left cerebellum posterior lobe, left inferior temporal gyrus, right lingual gyrus, left middle frontal gyrus, left angular gyrus, left cingulate gyrus, right angular gyrus and bilateral superior frontal gyrus，and decreased ReHo values in right anterior cingulate and left precentral gyrus. ROC curve analysis of each brain regions showed the accuracy of AUC was perfect except the right cerebellum posterior lobe. Nevertheless, there was no clear evidence of prominent relevance between the average ReHo values in brain areas and the clinical symptoms. Conclusion: CU caused dysfunctional adaption in different brain areas, which including relatively increased values and decreased values. This finding may help us take a further step in exploring the underlying pathologic mechanisms of CU.